Galvanização como tema motivador na disciplina de química tecnológica em um curso de engenharia de produção - Monassa, José Michel (Universidade Federal de São Carlos, 2016)
In technical visits to companies in Marilia and the region, the needs observed; on hiring a professional that would present previous knowledge of galvanization and its applications, it was proposed a reformulation of the menu of the Technological Chemistry discipline in the course of production engineering. This research was applied to the students of 2nd year/4th stage on studying Production Engineering at the Higher Education Institution. The research process involved: a) Utilizing galvanization as the main theme to motivate the learning process of the students; b) Increasing students’ prior knowledge of the galvanization theme; c) Bringing the labor market and the University together through technical visits to the companies of Marilia and the region; d) Proposing additional content to the menu of the Technical Engineering discipline. The exploratory research took a qualitative approach to assist in the collection and analysis of data. Data collection instruments were questionnaires that inquired on prior knowledge and then post-activities. The questionnaires consisted of two phases, one diagnostic and another one for evaluation. In the diagnostic phase, the students answered questions about previous knowledge of Electrochemistry and its applications. The second part of survey was administered after the instruction of new content. Based on the analysis of the answer categories and the correction of assessment tools applied to students, it was possible to observe the improvement in the learning process of the chemistry teaching. During the technical visits were observed the electroplating process for electrowinning and phosphating. The process of galvanizing phosphating is the most widely used in the industries of Marilia and region.
Keywords: Tratamento de superfícies metálicas; Galvanização a quente; Galvanização por eletrodeposição; Fosfatização; OUTROS